POTENTIAL OF MAGNETITE (Fe₃O₄) SYNTHESIZED FROM ZIRCON SAND WASTE AS METHYLEN BLUE DYE ADSORBENT - Marvin Horale Pasaribu; Karelius Karelius; Retno Agnestisia; Erwin Prasetya Toepak; Zimon Pereiz (Jurnal Inovasi Teknik Kimia, 2024)
Zircon sand mining is a major industry in Indonesia due to the country's vast zircon reserves. However, this industry also generates hazardous waste that can pollute the environment. This study aims to investigate the potential of magnetite (Fe₃O₄) synthesized from magnetic waste generated during zircon sand mining as an adsorbent for methylene blue dye removal. Magnetite was successfully synthesized via the co-precipitation method and characterized using XRD and FTIR. The synthesized magnetite demonstrated the ability to adsorb methylene blue from aqueous solutions with an adsorption efficiency of 68.52% after 80 minutes of contact time. The adsorption kinetics followed the pseudo second order model, evidenced by R² value of 0.9918, and the adsorption isotherm fitted the Langmuir model, indicating adsorption energy of 24.51 kJ/mol and adsorption capacity of 69.678 mg/g. These findings demonstrate the effectiveness of natural magnetite (Fe₃O₄) derived from zircon sand waste as an adsorbent for methylene blue dye removal. This research not only addresses the environmental issue caused by zircon sand mining waste but also develops a cost-effective and sustainable solution for methylene blue dye removal from wastewater.